“Spiritual and Moral Culture in the Higher Education” Expectations and fears (the results of ‘Christmas Educational Readings’ in PFUR) - Zh V Puzanova; M A Simonova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The article provides an overview of the key issues of the III International Conference “Spiritual and Moral Culture in the Higher Education” devoted to the discussion of the action plan to implement the National Strategy of Education Development until 2025. The authors consider the basic ideas of the key conference speakers’ presentations and present the results of the express-poll among the conference participants conducted to identify their expectations. The main leitmotif of all speakers’ presentations was as follows: the higher school is responsible for training the new generations of professionals - with high moral standards and responsibility for the fate of the country and one’s homeland. Young Russian citizens focused on fruitful activity can be raised only by joint efforts of the state, the church and society. It is extremely important to coordinate the efforts of the church and the state in the support and protection of the family, in combating extremism, and in forming high moral standards. ‘Christmas Readings’ is a good tradition established several years ago, which continues to bring together people interested in solving the most urgent problems in the educational sphere. The participants of the round tables discussed the issues of youth education and its impact on the country’s national security, the relationships of spiritual values and nation’s health, pedagogical aspects of spiritual and moral education of the youth, the impact of mass culture on the society, the student volunteer movement, spiritual and moral criteria of science.